Reproduction of porcine ear necrosis (ear-tip necrosis) following intradermal inoculation of pigs with Fusobacterium necrophorum - Matheus de O. Costa; Roman Nosach; Maite H. M. de Almeida (PLoS ONE, 2025)
Porcine ear necrosis (PEN) (also referred to as ear-tip necrosis, ETN) is a syndrome of global presence and unclear aetiology. Initially reported in the 1950s, many different infectious and non-infectious causes have been suggested as the causative(s) agent(s), but none has been confirmed in controlled studies. Here, we investigated the aetiology of PEN using pure culture of bacteria associated with lesions in controlled animal trials. A commercial farm with no history of ear-tip necrosis was identified and used as the source for 5-week-old pigs. Two independent trials were initially executed with identical designs. Piglets (=12/trial) were intradermally inoculated with either pure cultures of Staphylococcus hyicus or Fusobacterium necrophorum (left ear, n = 10) or sterile media (right ear, n = 10). Two pigs in each trial were not inoculated, serving as sentinels. A third trial used F. necrophorum as the inoculum, 3 pigs as sentinels and 9 as inoculated. All animals were clinically monitored daily following challenge, and an ear score was used to follow disease progression. All ears inoculated with S. hyicus remained lesion free. Four out of ten and 7/9 pigs challenged with F. necrophorum developed lesions undistinguishable from PEN, including necrosis and loss of portions of the ear pinna (P < 0.001). F. necrophorum was isolated from 4/10 and 7/9 pigs that developed necrotic lesions. Histopathology after resolution of necrosis revealed granulomatous tissue. Evidence presented here suggests that F. necrophorum causes PEN-like lesions, as seen in commercial barns. It is therefore suggested as the etiological agent of this syndrome.